2018
DOI: 10.2140/akt.2018.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Topological K-theory of affine Hecke algebras

Abstract: Let H(R, q) be an affine Hecke algebra with a positive parameter function q. We are interested in the topological K-theory of its C * -completion C * r (R, q). We will prove that K * (C * r (R, q)) does not depend on the parameter q, solving a long-standing conjecture of Higson and Plymen. For this we use representation theoretic methods, in particular elliptic representations of Weyl groups and Hecke algebras.Thus, for the computation of these K-groups it suffices to work out the case q = 1. These algebras ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Theorem 5.2 was one of the motivations for the author to write a paper about the K-theory of C * -completions of (extended) affine Hecke algebras [Sol5]. It enables us to show that the K-groups of the reduced C * -algebras of the above groups are torsion-free.…”
Section: Hecke Algebras From Bernstein's Progeneratorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theorem 5.2 was one of the motivations for the author to write a paper about the K-theory of C * -completions of (extended) affine Hecke algebras [Sol5]. It enables us to show that the K-groups of the reduced C * -algebras of the above groups are torsion-free.…”
Section: Hecke Algebras From Bernstein's Progeneratorsmentioning
confidence: 99%
“…By Morita invariance and Theorem 5.2, it suffices to show that the K-theory of the C * -completion of an extended affine Hecke algebra as in Theorem 5.2 is a finitely generated free abelian group. It was checked in [Sol5,(62)] that the Künneth theorem for topological K-theory [Sch] applies to such algebras. Thus we only need to prove the result when the underlying root datum is of type GL n , Sp 2n or SO 2n+1 and Γ is trivial, and when the root datum is of type (SO 2n ) e and Γ is as in (91).…”
Section: Hecke Algebras From Bernstein's Progeneratorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5] we gave a new proof of the Baum-Connes conjecture for the extended affine Weyl groups associated to compact connected semi-simple Lie groups, and showed that Langlands duality for the Lie groups induces an isomorphism of K-theory for the corresponding extended affine Weyl groups. In his consideration of the K-theory of Hecke algebras, Solleveld [7,8] determined the right hand side of the Baum-Connes conjecture for the affine Weyl groups associated to a number of Lie Groups including SL n (C). In order to do so he computed the extended quotients T n //W up to homotopy by constructing the quotients S n //W .…”
Section: Introductionmentioning
confidence: 99%